Microbiological Hazards in Dry Dog Chews and Feeds - Kępińska-Pacelik, Jagoda (Animals (Basel), 2021)
SIMPLE SUMMARY: Food-borne infectious agents can affect the health of pets. Good quality pet foods have high nutritional value, including microbiological quality. The most important biological hazards in feed are Salmonella, Enterobacteriaceae, pathogenic Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, Clostridium perfringens, Clostridium botulinum, Aeromonas, and Campylobacter. Other biological hazards of feed are the mycotoxin-producing molds. Although in some studies the level of mycotoxins in the foods does not exceed the maximum allowable amounts, long-term ingestion of mycotoxins may have adverse health effects, as these compounds accumulate in the tissues of animals. Animal by-products or derived products can also be a source of the above-mentioned risks. Pet foods products can also be a source of human infection. The close coexistence of humans and animals means that ensuring the safety of pet foods should be a priority. ABSTRACT: Nowadays, dogs are usually equally treated with other family members. Due to the growing caregivers’ awareness, the pet foods industry is changing dynamically. Pet foods are manufactured with a myriad of ingredients. Few authors of scientific papers deal with the topic of foods products’ safety for pet animals, assessed from the perspective of their caregivers. Despite the many methods of producing foods of the highest quality, there are still cases of contamination of pet foods and treats. In the case of dried chews for dogs, bacteria of the genus Salmonella are the most common risk. In the case of both dry and wet foods, in addition to many species of bacteria, we often deal with mold fungi and their metabolites, mycotoxins. This article presents selected microbiological risks in dog foods and treats, and analyzes the Rapid Alert System for Food and Feed (RASFF) system (2017–2020) for pathogenic microorganisms in dried dog chews, treats and foods. In this period, pet food-related notifications were registered, which were categorized into different types. Analyzing the RASFF notifications over the period, it has been shown that there are still cases of bacterial contamination of dog foods and treats, while in terms of the overall mycotoxin content, these products may appear safe.